Analisis Psikologis terhadap Perilaku Hakim dalam Mengambil Keputusan - Khairul Hidayatullah; Abdurrahman; Alfia Roza; Fabrizio; Resky; Rian Prayudi Saputra (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This article aims to provide an in-depth understanding of the psychological challenges judges face in decision making, as well as their impact on individuals, society and the legal system. The method used is a literature review that analyzes theories, research and related references to evaluate cognitive, emotional and social factors that influence judge behavior. The discussion shows that cognitive bias, emotional stress, and external influences can influence a judge's objectivity, while experience and education play an important role in making fair decisions. Judges' decisions have significant implications, from changing the fate of individuals to strengthening or undermining public trust in the legal system. In conclusion, wise, professional decision making, and based on thorough analysis is necessary to maintain judicial integrity and social stability.